2002
DOI: 10.1093/hmg/11.9.993
|View full text |Cite
|
Sign up to set email alerts
|

Different RPGR exon ORF15 mutations in Canids provide insights into photoreceptor cell degeneration

Abstract: The canine disease, X-linked progressive retinal atrophy (XLPRA), is similar to human RP3, an X-linked form of retinitis pigmentosa, and maps to the same region in the X chromosome. Analysis of the physical map of the XLPRA and RP3 intervals shows a high degree of conservation in terms of genes and their order. We have found different mutations in exon ORF15 of the RPGR gene in two distinct mutant dog strains (XLPRA1, XLPRA2). Microdeletions resulting in a premature stop or a frameshift mutation result in very… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
186
0
9

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(205 citation statements)
references
References 29 publications
5
186
0
9
Order By: Relevance
“…17 On the other hand, XLPRA is caused by microdeletions in exon ORF15 of RPGR, and the mutation causing a frameshift has a severe, and aggressive early-onset cone/rod disease phenotype similar to what is found in RPGR/XLRP patients. 6,18 Previous studies have shown that sequences upstream of the human red or long wavelength (L) opsin gene contain a core promoter with a locus control region (LCR) that confers expression in cones of transgenic mice. 19,20 When a truncated version of the upstream sequences was incorporated into a recombinant adenoassociated viral vector (rAAV) of serotype-5 (rAAV5), this promoter targeted green fluorescent protein (GFP) expression to cones in the mouse, rat, ferret, guinea pig and squirrel monkey.…”
Section: Introductionmentioning
confidence: 99%
“…17 On the other hand, XLPRA is caused by microdeletions in exon ORF15 of RPGR, and the mutation causing a frameshift has a severe, and aggressive early-onset cone/rod disease phenotype similar to what is found in RPGR/XLRP patients. 6,18 Previous studies have shown that sequences upstream of the human red or long wavelength (L) opsin gene contain a core promoter with a locus control region (LCR) that confers expression in cones of transgenic mice. 19,20 When a truncated version of the upstream sequences was incorporated into a recombinant adenoassociated viral vector (rAAV) of serotype-5 (rAAV5), this promoter targeted green fluorescent protein (GFP) expression to cones in the mouse, rat, ferret, guinea pig and squirrel monkey.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has shown that CNTF delivered through intravitreal injections (Pearce-Kelling, unpublished study), or by means of an ECT device (Tao et al, 2002), rescues photoreceptors in the rcd1 dog, an early and rapidly progressing large animal model of RP caused by a stop mutation in PDE6B. The purpose of the present study was to determine whether intravitreal injections of CNTF could provide a similar neuroprotective effect in XLPRA2, an early onset model of X-linked RP caused by a frameshift mutation in RPGR exon ORF15 (Zhang et al, 2002;Ferreira, 2005;Khanna et al, 2005). Recently, we reported the morphologic retinal changes, and the kinetics of photoreceptor cell death, that occur during the course of this disease .…”
Section: Introductionmentioning
confidence: 85%
“…All animals were bred and housed at the Retinal Disease Studies Facility (RDSF, University of Pennsylvania, New Bolton Center, Kennett Square, PA). Their genotype was determined either from the known status of their progenitors, or from genetic testing for the disease-causing mutation (Ray et al, 1994;Zhang et al, 2002). All animals underwent an initial ocular examination that confirmed the absence of clinically evident abnormalities.…”
Section: Animalsmentioning
confidence: 99%
“…The protocols were approved by the Institutional Animal Care and Use Committee of the University of Pennsylvania. RPGR mutant (XLPRA2) (28,29) and WT dogs were used to characterize the natural course of ONL thinning as a function of age (16) and the response to subretinal injections with an AAV2/5 vector (64) carrying a stabilized human RPGR 1-ORF15 cDNA under the control of a human IRBP promoter (30,65). The stabilized human RPGR 1-ORF15 cDNA (stable hRPGR) contained seven in-frame deletions, one 3-bp insertion, and 65-bp substitutions spread throughout the AG-rich region of exon ORF15 compared with the published (GenBank: NM_001034853) human RPGR 1-ORF15 sequence (34).…”
Section: Methodsmentioning
confidence: 99%
“…The natural course of RPGR-XLRP disease is severe, with males showing loss of night vision in the first decade of life (23). The disease onset in the naturally occurring or Rpgr KO mouse models is very late (23)(24)(25) as it corresponds to 35 human years (26), whereas the disease onset in two naturally occurring canine models of RPGR-XLRP (27)(28)(29) are earlier and correspond better to the human disease time course. Gene augmentation delivered by means of an adeno-associated viral (AAV) vector has been shown to be efficient in both the dog and mouse models (30,31).…”
Section: Significancementioning
confidence: 99%